Food Price, Food Security and Dietary Diversity: A Comparative Study of Urban Cameroon and Ghana. (27th June 2017) - KC, Krishna Bahadur; Legwegoh, Alexander F.; Therien, Alex; Fraser, Evan D.G.; Antwi‐Agyei, Philip
Abstract: This paper contributes to the urban food security literature by presenting the results of 600 household surveys conducted in Ghana and Cameroon. In this, we show how dietary diversity, which is a well‐developed proxy for food security, is similar in both countries but varies significantly based on household demographic characteristics. In particular, smaller, better‐off and more educated households were likely to have higher levels of dietary diversity and were less likely to respond to rising food prices by reducing diets or shifting buying patterns. In addition, households that live in 'primary' cities that are large and well integrated into global markets also enjoyed higher levels of dietary diversity. This research contributes to debates around whether or not food security is enhanced by being integrated into global markets or whether it is better served through national or regional food systems. The evidence uncovered here suggests that for well‐off households, integration into global markets is probably preferable as such households enjoy more diverse diets. Copyright © 2017 John Wiley & Sons, Ltd.